Valuation of foreign direct investment positions - final report - Roger De Boeck; Sebastian Hügelschäffer; Stephen McDonagh; Patricia Portero; Dominique Nivat; Valeria Pellegrini; Erika Veitzné Kenyeres; Rini Hillebrand; René Dell'mour; Márcio Filipe Mendes Mateus; Ciara Williams-Fletcher; Neil Bannister; et al. (European Central Bank (ECB), 2013)
The mandate of the Task Force on Valuation of Foreign Direct Investment (FDI) Positions was to review the methods to value direct investment positions stated in Annex III of the Guideline ECB/2011/23 on External Statistics. In particular, the work of the Task Force was focused on reviewing recent developments that may justify amendments to the current method and assessing whether new methods to be applied in the national contributions to the euro area aggregate would lead to a more reliable international investment position (i.i.p.), in particular by increasing the consistency in the valuation of FDI assets and liabilities. The report concluded that in some cases where the use of own funds at book value (OFBV) data would lead to significant biases in the national net i.i.p., other valuation methods than OFBV could be used, adding that national compilers shall exchange information on those positions with the other relevant Member State(s). National compilers should then consider, on a case-bycase basis, adjusting the valuation of those positions in order to strive for a consistent recording of these investments by counterpart EU countries. The Task Force's final report was considered and approved by the Working Group on External Statistics at its meeting on 30 and 31 October 2012.
Keywords: A39; C82; F21; 330; balance of payments statistics; FDI valuation; foreign direct investments statistics; market value; own funds at book value